Implementasi SAMSAT Delivery Service dalam Meningkatkan Kualitas Pelayanan Publik - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; PUTU ADITYA FERDIAN ARIAWANTARA (FISIP UWP, 2010)
Public administration have important task to provide public services in any sectors, to collect taxes from citizens, and other services to fulfill any citizens needed based on institutional law. Based on the values that make it easy for citizens in paying taxes, then the paradigm shift that emerged in the era of bureaucratic reform, particularly in order to improve the quality of public services in Indonesia is